2021
DOI: 10.7759/cureus.18358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Diseases and Conditions on Oral Health-Related Quality of Life: A Narrative Review of Studies Conducted in the Kingdom of Saudi Arabia

Abstract: Oral health-related quality of life (OHRQoL) is a novel concept that has evolved over the past two decades. The World Health Organization (WHO) has also recognized it as a significant part of the Global Oral Health Program (2003). Information on OHRQoL gives better understanding about feelings and perceptions on an individual level. It also helps us to understand the impact of oral health on the lives on the patients and their family. It is now well documented that oral diseases and conditions impact people’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“… 2 Oral diseases such as caries, dental fluorosis, tooth loss, periodontal disease, dental injuries, oral cancer, dental anomalies, craniofacial disorders, and many more have got a negative impact on oral health-related quality of life (OHRQoL). 3 Research has shown that oral health status is associated with OHRQoL in the general population. 4 Oral health is perceived as an essential component of overall quality of life, and OHRQoL refers to a person’s perceived health, well-being, and quality of life related to oral conditions and function.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Oral diseases such as caries, dental fluorosis, tooth loss, periodontal disease, dental injuries, oral cancer, dental anomalies, craniofacial disorders, and many more have got a negative impact on oral health-related quality of life (OHRQoL). 3 Research has shown that oral health status is associated with OHRQoL in the general population. 4 Oral health is perceived as an essential component of overall quality of life, and OHRQoL refers to a person’s perceived health, well-being, and quality of life related to oral conditions and function.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeon General Report on Oral Health reported that oral health is a fundamental part of general health and plays a significant role in the overall improvement in well-being in a person’s life [ 7 ]. Therefore, it is important to evaluate the extent of oral diseases and the presence of oral manifestations to establish an adequate oral health care setting to understand children’s oral health care needs, provide routine dental visits, and address the barriers to adequate oral health care [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OHRQoL can profoundly impact children's lives, influencing the ability to engage in day-to-day activities and learning, school performance, and social interactions. Dental caries, malocclusion, and other oral diseases can cause discomfort, eating difficulties, and embarrassment, thus reducing the child's quality of life [3][4][5]. Therefore, addressing and preventing such problems from an early age is crucial.…”
Section: Introductionmentioning
confidence: 99%